Mechanosensitive Piezo channels in mineralized tissues: emerging roles in osteodental adaptation and disease - Dong, Junchi; Li, Ran; Chen, Yuhuang; Zhu, Guixin; Liang, Xing (Frontiers in Cell and Developmental Biology, 2025)
Bone and dental tissues are highly mineralized and mechanically sensitive hard tissues. They detect and respond to mechanical forces via mechanosensitive Piezo channels, modulating physiological and pathological processes. While Piezo mechanobiology has been explored, systematic comparison of their roles across bone and dental tissues, particularly their potential crosstalk in adaptation and disease, remains underexamined in existing reviews. This review consolidates recent advances in Piezo channel biology, clarifying their structural properties, tissue-specific distribution, and functional roles in mineralized tissues. Emerging evidence highlights Piezo channels as key mechanotransducers ubiquitously expressed in skeletal and dental cellular populations. By mediating distinct mechanotransduction pathways, Piezo1 and Piezo2 modulate diverse processes, including bone remodeling, osteoblast-osteoclast communication, dental stem cell differentiation, dental hard tissue mineralization, and orthodontic tooth movement. Furthermore, their dysregulation is implicated in pathologies such as osteoporosis, pulpitis, and dentin hypersensitivity. The elucidated mechanisms establish a theoretical framework for Piezo-mediated mechanotransduction in cellular adaptation and disease progression. By integrating molecular mechanisms with regenerative applications across both osseous and dental contexts, this review advances understanding of shared mechanobiological principles in mineralized tissues and highlights translational relevance for skeletal and dental therapies. These insights align with mechanobiology and tissue engineering research, supporting future development of mechanosensitive interventions.